Pengaruh Dewan Komisaris, Dewan Pengawas Syariah, Dan Struktur Modal Terhadap Kinerja Keuangan Pada perbankan Syariah Periode 2021-2023 - Irsyad Alief Gutawa; Ratnawati Raflis; Indrayeni (CV. ITTC INDONESIA, 2025)
This study analyzes the influence of the Board of Commissioners, Sharia Supervisory Board, and Capital Structure on Financial Performance in Islamic Banking in Indonesia. A case study was conducted on Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) registered with the Financial Services Authority (OJK) during the 2021–2023 period. The research aims to examine the partial and simultaneous effects of each independent variable on financial performance, measured by Return on Assets (ROA). The research population includes 38 Islamic banks, with a sample of 21 banks (11 BUS and 10 UUS) selected using purposive sampling based on the availability of complete annual reports. Data were analyzed using multiple linear regression with classic assumption tests and hypothesis testing.The results indicate: (1) The Board of Commissioners has a significant effect on financial performance, (2) The Sharia Supervisory Board has no effect on financial performance, (3) Capital Structure (measured by the Debt to Asset Ratio) has a significant effect on financial performance, and (4) The Board of Commissioners, Sharia Supervisory Board, and Capital Structure collectively influence financial performance.